Cave Art, Perception and Knowledge - Rosengren, M. author. aut Link
XIII, 169 p.
Keywords: Using the example of prehistoric paintings discovered in the late 19th century in Spain and France Cave Art, Perception and Knowledge inquires into epistemic questions related to images, depicting and perception that this rich material has given rise to. The book traces the outline of the doxa of cave art studies.